Applicability of green fluorescence protein in the study of endothelin converting enzyme-1c trafficking - Kuruppu, Sanjaya (Wiley Subscription Services, Inc., A Wiley Company, 2013)
Endothelin-1 (ET-1) is one of the most potent peptide vasoconstrictors known. It is produced upon the cleavage of its precursor big endothelin-1 by endothelin converting enzyme-1 (ECE-1). Production of ET-1 is thought to be dependent upon the expression of ECE-1 at the cell surface. Therefore, mechanisms inducing the trafficking of ECE-1 to the cell surface have been the focus of recent research. This research has identified phosphorylation of the cytoplasmic region of ECE-1 as a main cellular signal inducing its trafficking to the cell surface. Previous studies have used green fluorescent protein (GFP) tagged ECE-1 to monitor phosphorylation induced trafficking of ECE-1 to the cell surface. However, it has been speculated that the addition of the GFP tag can itself alter enzyme activity and phosphorylation of ECE-1, and hence the suitability of GFP or any other protein tag in studying ECE-1 distribution and trafficking. ECE-1c is the most widely expressed isoform in endothelial cells. We therefore expressed ECE-1c with a GFP tag either at the N or C-terminus of ECE-1c. Catalytic activity and effect on protein kinase C (PKC) induced phosphorylation was compared between the two chimeras and wild-type ECE-1c. Our results indicate that positioning of the GFP tag on the C-terminus abrogates activity without effecting PKC-induced phosphorylation. However, GFP tag on the N-terminus has the opposite effect. Results of this study shed light on the applicability of GFP or perhaps other protein tags in studying ECE-1c distribution and trafficking.